Medullary Thyroid Carcinoma With Elevated Serum CEA and Normal Serum Calcitonin After Surgery: A Case Report and Literature Review - Chen, Li; Zhao, Ke; Li, Fuxin; He, Xianghui (Frontiers in Oncology, 2020)
Background Medullary thyroid carcinoma (MTC) is a relatively rare malignant tumor subtype originated the parafollicular C cells of the thyroid gland, producing tumor markers including calcitonin (Ctn), carcinoembryonic antigen (CEA), and chromogranin A. Preoperative serum Ctn and CEA value is important for assessing disease burden, postoperative serum Ctn and CEA can help to determine whether there are recurrence and distant metastasis. Case Presentation We report a rare case in which the CEA level continued to increase and the Ctn value was normal after total thyroidectomy and central lymph node dissection in a MTC patient. The patient was asymptomatic during one and half year follow-up until lateral lymph node metastasis was revealed. However, the CEA level raised again after lateral neck lymph node dissection and bone metastases were found by 18F-FDG PET-CT. Conclusion This case reminded us the recurrence of MTC should be suspected for patients with simply elevated CEA after surgery for MTC. Differential diagnosis of other malignant tumors and timely lymph node biopsy is of great significance for management.